การประเมินความต้องการจำเป็นในการพัฒนาการทำวิจัย เชิงปฏิบัติการในชั้นเรียนของครูในระดับมัธยมศึกษา - อภิรักษ์ โภชพิพิธ (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2018)
This research aims to analyze the operating conditions of the teachers used to do classroom action research, to analyze the problems of doing classroom action research and to assess suitably the needs for development of classroom action research of teachers by classifying each step of classroom action research. The samples used in this study were 376 people from multi-stage random (population 1,934 people, the confidence level of 95% of the sample must be more than 322 people).The research instruments created by synthesis the methods that the teachers used in doing classroom action research. The tool were divided into 3 sections, general information, conditions of doing classroom action research and problem condition of doing classroom action research. The reliability of the questionnaire in each section were 0.9797 and 0.9768 respectively. The data was analyzed by using basic statistics and Modified Priority Needs Index (PNImodified) to arrange the importance and the needed results. The findings of this research were as follows : 1. The analysis of the operating conditions of doing classroom action research. The highest condition that the teachers always do is defining some issues to run the classroom action research and the figure out plan. By contrast the lowest condition that the teachers always do is reflecting after the performance.